Early protection in sheep against intratypic heterologous challenge with serotype O foot-and-mouth disease virus using high-potency, emergency vaccine. Issue 3 (9th January 2015) - Horsington, Jacquelyn; Zhang, Zhidong; Bittner, Hilary; Hole, Kate; Singanallur, Nagendrakumar B.; Alexandersen, Soren; Vosloo, Wilna
Abstract In 2009–2011, spread of a serotype O foot-and-mouth disease virus (FMDV) belonging to the South East Asia topotype led to the culling of over 3.5 million cattle and pigs in Japan and Korea. The O1 Manisa vaccine (belonging to the Middle East-South Asian topotype) was used at high potency in Korea to limit the expansion of the outbreak. However, no data are available on the spread of this virus or the efficacy of the O1 Manisa vaccine against this virus in sheep. In this study, the early protection afforded with a high potency (>6 PD50) FMD O1 Manisa vaccine against challenge with the O/SKR/2010 virus was tested in sheep. Sheep (n = 8) were vaccinated 4 days prior to continuous direct-contact challenge with donor sheep. Donor sheep were infected with FMDV O/SKR/2010 by coronary band inoculation 24 h prior to contact with the vaccinated animals, or unvaccinated controls (n = 4). Three of the four control sheep became infected, two clinically. All eight O1 Manisa vaccinated sheep were protected from clinical disease. None had detectable antibodies to FMDV non-structural proteins (3ABC), no virus was isolated from nasal swabs, saliva or oro-pharyngeal fluid and none became carriers. Using this model of challenge, sheep were protected against infection as early as 4 days post vaccination.